Lignite Coal Co-combustion Performance with Banana Tree Waste, Tree Leaves and Cow Dung Manure Blends for Emission Reduction During Power Generation - Siddique, Mohammad; Abubakar, Abdulhalim Musa; Soomro, Suhail Ahmed; Memon, Hafeez-ur-Rehman; Zakarya, Irnis Azura; Sylvain, Tome (Journal of Mechanical Engineering, Science, and Innovation, 2024)
Biomass blends with lignite coal (LC) normally have better co-combustion property, which in turn improves electricity output and reduces emissions. Given that global warming caused by emissions of CO, NOx, SO2, CO2 and NO from manufacturing industries and power plants is growing, this study seeks to find environmentally friendly alternative fuel to be employed. Here, suitable particle size of LC was combined with tree leaves (TL), cow dung manure (CDM) and banana tree waste (BTW) in the ratio of 90:10, 80:20, 70:30 and 60:40 each to form 16 samples (4 single and 12 blends). Thermal and combustion characteristics studies conducted during their combustion in an electric muffle furnace at 700  helped declare all blends as favorable with higher heating values ranging from 521179-892952 Btu/lb to be used as fuel in coal-powered plants. For moderately low emissions of flue gases, better thermal combustion property, high heating value (i.e., 892952 Btu/lb) and the highest electricity output, LC90 + CDM10 is the best blend discovered by this study. However, LC utilization still defeats the best performing blend in terms of lower emission with LC80 + TL20 having tolerably closer emission level compared to LC and a good substitute if emission must be kept as same level. Due to this shortcoming, further ratio adjustment or optimization and catalyst/additive addition is recommended to bring the emissions to environmentally friendly levels. It is also paramount to analyze the samples for chlorine concentrations to keep at desired composition in order not to risk a high temperature chlorine corrosion during co-combustion.